Traditional Border Crossing Agreement in the Settlement of the Noelbe-si-Citrana Boundary Dispute - Handrianus Nino; Remigius Seran (IHSA Institute, 2026)
The Noelbesi-Citrana boundary dispute between Indonesia and Timor-Leste is one of the biggest challenges in bilateral relations between the two countries. Differences in interpretation of historical documents, such as the 1904 Dutch-Portuguese Agreement, have created uncertainty regarding the boundary. In efforts to resolve this dispute, traditional mechanisms such as the Traditional Border Crossing Agreement (TBCA) have become a promising alternative. This article examines the role of this traditional approach in facilitating cross-border relations, reducing tensions between communities, and supporting formal diplomatic efforts. By highlighting the practices, benefits, and challenges of implementing traditional border crossing agreements (through tok tabua, mapua mamat, natoni, and tiun menu), this article emphasizes the importance of collaboration between local communities and the government in finding peaceful and sustainable solutions. These findings are expected to provide new insights for resolving boundary disputes in other regions. In this study, the researchers collected data through a survey using questionnaires and interviews. The survey results will be followed by a Forum Group Discussion (FGD) to further examine the desired objectives. Data analysis was conducted using the Craswell method, which essentially includes data preparation, tabulation, general sense, synthesis, and interpretation